AB0013 Is there immune disregulation in non-sjÖgren sicca syndrome? a study of blood lymphocyte subpopulations. (15th June 2017) - Barcelos, F; Martins, C; Nunes, G; Lopes, T; Patto, J Vaz; Amaral, J; Branco, JC; Borrego, LM
Abstract : Background: A large number of patients with sicca syndrome not fulfilling Sjögren's syndrome (SS) classification criteria, present manifestations of autoimmunity, like arthritis, Raynaud's, rash or hematologic disturbances, and have anti-nuclear antibodies, lacking however more specific antibodies. The designation Undifferentiated Connective Tissue Disease was coined to refer to those patients, and some will eventually progress to a definite disease, of which SS would be a likely candidate. Immune cell disturbances could be progression markerr, since diseases like pSS have distinct lymphocyte profiles. Objectives: We aim to study the circulating lymphocyte subsets in non-Sjögren sicca patients (n-SS), and compare them with pSS and healthy controls. Methods: We included 65 n-SS patients, 53 pSS patients (2002 AECG criteria) and 22 healthy controls. Lymphocyte subsets were characterized by flow cytometry, including follicular and regulatory T cells and naïve, mature, memory, plasmablasts and regulatory B cells. Statistical analysis was performed with GraphPad, and significance was considered for p<0.05 Results: Comparing to controls, n-SS patients had lower counts of T cells (p=0.016), with lower CD4 (p=0.0028), however that difference was not as pronounced as between SS and controls. n-SS patients had higher percentages of CD4 (p=0.0005) and lower CD8 percentages (p=0.0009) than pSS. Additionally, there was a decrease in absolute counts of Tregs (p=0.0028) in n-SS patients compared to controls, which was less pronounced than the comparison between SS and controls (p=0.0008). Th17 cells were decreased in SS compared to controls (p=0.0005), but not in-SS patients. Compared with controls, both n-SS and SS patients presented decreased absolute count (p=0.0001 and p<0, 0001, respectively) of CXCR5 + Tfh cells, with no differences between n-SS and SS patients. However, higher levels of IL21 + CD4 T cells and Tfh1 cells were found comparing SS patients with both controls (p=0, 0209 and p=0, 0092 respectively) and n-SS patients (p=0, 0051 and 0, 0028 respectively). Absolute counts of memory, unswitched and switched memory cells in n-SS patients present intermediate levels between controls with significantly higher levels, and SS patients with significantly lower levels. Accordingly, using the Bm1–5 classification, we have found decreased Bm1 (p=0.004), eBm5 (Abs, p=0.0273) and Bm5 cells (Abs, p=0.0444) in n-SS patients compared to controls. Though not significant, there was an increase in eBm5 (Abs, p=0.063) and Bm5 cells (Abs, p=0.05) in n-SS compared to SS patients. Again, CD24 + CD27 + Bregs were also decreased in n-SS patients compared to controls (p=0.036), but increased in n-SS compared to SS patients (p=0, 0007). Conclusions: Our data showed that n-SS patients present immune disregulation, represented by alterations in the B cell compartment but also in Tfh subset, known to modulate the humoral immune response. Although less pronounced, these modifications resemble the ones found in SS patients. Wether n-SS is a stage in the evolution to SS remains to be clarified. The identification of a characteristic disregulation of the immune system in n-SS could be usefull for diagnostic and prognostic purposes. Disclosure of Interest: None declared